The Meanings of Alzheimer’s Disease - Timothy Daly (Philosophy of Medicine)
Alzheimer’s disease emerged around the 1900s as a rare disease that became synonymous with common dementia by the 1980s. In the 2010s, in vivo biomarkers of Alzheimer’s pathophysiology then led researchers to emphasize the presymptomatic biology of Alzheimer’s biomarkers, thus decentering dementia. Three consensus definitions were elaborated around biomarkers, and were rearticulated in 2024: biomarker-determined Alzheimer’s disease; biomarker-informed “clinical-biological” Alzheimer’s disease; and biomarker-independent, “all-cause” dementia. I consider their differences to hinge on the questionable legitimacy of the Alzheimer “biomarkerization” of aging. I encourage a focus on the actionable concept of brain health beyond Alzheimer’s to motivate equitable health promotion.